Finite and infinite dosing: Difficulties in measurements, evaluations and predictions - Selzer, Dominik; Abdel-Mottaleb, Mona M.A.; Hahn, Tsambika; Schaefer, Ulrich F.; Neumann, Dirk (Advanced drug delivery reviews, 2013)
Due to the increased demand for reliable data regarding penetration into and permeation across human skin, assessment of the absorption of xenobiotics has been gaining in importance steadily. In vitro experiments allow for determining these data faster and more easily than in vivo experiments. However, the experiments described in literature and the subsequent evaluation procedures differ considerably. Here we will give an overview on typical finite and infinite dose experiments performed in fundamental research and on the evaluation of the data. We will point out possible difficulties that may arise and give a short overview on attempts at predicting skin absorption in vitro and in vivo. [Display omitted]